Silage additive update: 1984 - Bolsen, K.; Hinds, M.; Brethour, J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Numerous commercial silage additives, whose manufacturers claim will improve silage quality, are available to Kansas farmers and ranchers. We believe that these claims must ultimately be documented with farm-scale research. To date, Manhattan and Ft. Hays farm-scale silo results clearly indicate that a few silage additives do improve silage quality and are cost-effective. Several of them have consistently reduced “in silo” losses. But results probably will not be favorable with all additives under every farm condition. Nor will research results obtained with one commercial product in our trials also apply to other products on the market, however similar in ingredient formulation.
Keywords: Beef; Silage; Silo; Quality